Measuring the Grit Scale for Teachers of Children With Special Needs in Indonesia: Mengukur Skala Grit untuk Guru Anak Berkebutuhan Khusus di Indonesia - Syifa'a Rachmahana, Ratna; Chirzin, Muhammad; Bashori, Khoiruddin; Purnomo, Halim (Universitas Islam Indonesia, 2023)
Grit is the ability of individuals to exhibit commitment, persistence in effort, as well as passion to attain long-term objectives. The research on grit in Indonesia has remained limited to students, and the investigation among teachers was popularized by Baraquia (2020). This aligns with the emergence of performance appraisal systems for teachers in the Philippines to support the continuous development of the teaching profession. Therefore, this research aimed to measure the validation of the Teacher's Grit Scale (TGS) in the Indonesian version. The adaptation process was carried out following the guidelines from the International Test Commission (ITC) using the Confirmating Factor Analysis (CFA) method. CFA is the most reliable analytical method so far in testing the construct validity of a measurement tool in the fields of psychology, education, and social sciences. Data were collected from 301 teachers of children with special needs (CSN) selected by accidental sampling based on CFA test analysis using JASP. The results showed that the model fulfilled the criteria for fit, namely RMSEA .076, CFI .929, TLI .913, RNI .929, GFI .995, and SRMR .049. Therefore, TGS-Indonesia was valid and reliable for measuring grit in CSN teachers, and the discussion and implications were presented in the subsequent research.